Ancestral Religious Recognition an Effort to Build Indonesia without Discrimination - Tijani, Achmad (Pascasarjana IAIN Pontianak, 2017)
Samsul Ma’arif, Dynamics of Ancestral Religious Recognition in Religious Politics in Indonesia. Yogyakarta: CRCS UGM, 2017 Juridically Indonesia has identified itself as a religious country. An important element which states that it is manifested in Pancasila as the foundation of the state in the first principle, namely the belief in the oneness of God. The formalization of the element of belief in all of the nation's history is not a flawless one. One of the criticisms that is not taken seriously by most components of the nation is a derivative form of the first polarized first principle in the birth of official religions recognized by the state. Polarization is arguably very exclusive, which eventually, will deny the existence of other beliefs that grow in the community. As a consequence, there arises a pejorative narrative in all its forms to those outside the official state religions. Even the most unnecessary things happen, as violent acts which very likely result from the exclusive polarization.